2018
DOI: 10.1161/jaha.118.008970
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance and New‐Onset Heart Failure: A Longitudinal Study of >500 000 Individuals From the General Population

Abstract: BackgroundHeart failure constitutes a high burden on patients and society, but although lifetime risk is high, it is difficult to predict without costly or invasive testing. We aimed to establish new risk factors of heart failure, which potentially could enable early diagnosis and preemptive treatment.Methods and ResultsWe applied machine learning in the UK Biobank in an agnostic search of risk factors for heart failure in 500 451 individuals, excluding individuals with prior heart failure. Novel factors were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…7,28,31 Bioimpedance is defined as the ability of tissue to impede electric current, and is related to the amount of fluid accumulation in body tissue. 36 Combined with the recent finding that leg bioimpedance is associated with risk for heart failure 37 , these novel predictors suggest a link between high-volume venous reflux, increased hydrostatic pressure, and resulting venous hypertension.…”
Section: Discussionmentioning
confidence: 94%
“…7,28,31 Bioimpedance is defined as the ability of tissue to impede electric current, and is related to the amount of fluid accumulation in body tissue. 36 Combined with the recent finding that leg bioimpedance is associated with risk for heart failure 37 , these novel predictors suggest a link between high-volume venous reflux, increased hydrostatic pressure, and resulting venous hypertension.…”
Section: Discussionmentioning
confidence: 94%
“…In patients with HF, use of the Edema Guard Monitor (CardioSet Medical) combined with a symptom diary was associated with increases in self-behaviour score for 30 days after hospital discharge 49 . In an analysis of more than 500,000 individuals in the UK Biobank, a machine learning model revealed that leg bioimpedance was inversely associated with HF incidence 50 . Numerous innovative and non-invasive tools can be used to detect leg impedance, such as sock-based sensors 51 .…”
Section: Innovative Biosensors For Hf Detectionmentioning
confidence: 99%
“…We also demonstrated that a predictive algorithm analyzing daily bioimpedance measures achieved good performance for predicting recurrent acute decompensated heart failure [ 12 ]. Lindholm et al [ 22 ] also performed a longitudinal study including over 500,000 participants and determined that leg bioimpedance was inversely correlated with new-onset heart failure and that by combining the leg bioimpedance with clinical parameters such as age, sex, and history of myocardial infarction, accurate prediction of heart failure could be achieved. In another study [ 23 ] on participants with congenital heart disease, bioelectrical impedance correlated with heart failure severity.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has shown that transthoracic bioimpedance can be measured daily with fluid accumulation vests using conventional electrodes, and a predictive algorithm analyzing daily bioimpedance parameters showed reasonable performance in predicting recurrent heart failure events, including hospitalization, diuretic uptitration, and worsening heart failure symptoms [ 12 ]. Lindholm et al [ 22 ] determined that leg bioimpedance was inversely correlated with heart failure incidence, and by combining leg bioimpedance with demographic information, they obtained accurate heart failure predictions. Sato et al [ 23 ] evaluated parameters from bioelectrical impedance analysis in participants with congenital heart disease and determined that the edema index obtained from bioelectrical impedance analysis could also be a marker for heart failure severity.…”
Section: Introductionmentioning
confidence: 99%